Copper-Mediated Late-Stage Iodination and 123I-Labelling of Triazole-benzimidazole Bioactives - Fjellaksel, Richard; Sundset, Rune; Riss, Patrick J.; Hansen, Jørn H. (Synlett, 2018)
The copper-mediated azide-alkyne cycloaddition has been studied to achieve late-stage introduction of iodine onto novel triazole-benzimidazole Gonadotropin Releasing Hormone (GnRH)-receptor antagonists. Moreover, the reaction conditions can affect a direct regioselective C–H iodination of the benzimidazole, leading to a range of novel iodo-analogues. The methodologies are powerful strategies for late-stage 123I-labelling of complex bioactives. Our investigations have generated two highly promising 123I-labelled radiotracer candidates that retain high affinities for the GnRH-receptor.
Keywords: CuAAC; GnRH antagonist; radiotracer; triazoles; 123I-labeling